The Influence of Religiosity and Obedience Pressure on the Intention to Commit Fraud in Sharia Financial Institutions in Gorontalo City - Ajenk Dizca Lalahu; Niswatin; Surya Handrisusanto Ahmad (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to determine the influence of the Religiosity variable and the Obedience Pressure variable on the Intention to Commit Fraud in Sharia Financial Institutions of Gorontalo City. The method used in this study is a quantitative method with primary data obtained from a questionnaire whose measurement uses the Likert scale. The sample collection process used a purposive sampling technique with a total sample of 42 respondents spread across four Islamic financial institutions in Gorontalo City, namely Bank Syariah Indonesia, Bank Muamalat Indonesia, AMITRA-FIF Group, and Pegadaian Syariah. The data analysis technique in this study uses multiple linear regression analysis operated through the SPSS program. Based on the results of the study, religiosity did not have a significant effect on the intention to commit fraud in Islamic financial institutions in Gorontalo City, while the pressure of obedience had a positive and significant effect. Simultaneously, religiosity and obedience pressure had a positive and significant effect on the intention to commit fraud, explained by an Adjusted R Square value of 35.3% while the other 64.7% was contributed by other variables outside the research model.